Scalability 4.0 as the main rent in Industry 4.0: the case study of Amazon - Niemczyk, Jerzy; Trzaska, Mateusz (Skalowalność 4.0 jako źródło korzyści w przemyśle 4.0. Studium przypadku firmy Amazon, 2019)
This paper discusses the research problem concerned with identifying the source of the economic efficiency of enterprises operating in the conditions of Industry 4.0. The purpose of this study was to describe scalability 4.0 using the example of Amazon, a global company. In the authors’ opinion, it can serve as an example of an organisation which consciously implements a strategy of building value relying on various forms of economies of scale based on contemporary Industry 4.0 technologies. In particular, the authors of this paper point to the capacity to achieve economies of scale, the network effect, the long tail effect, and the Big Data effect by Amazon as a whole and by individual Amazon Group entities
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 2 (52), s. 69-84
Keywords: scalability; strategic management; Industry 4.0; Amazon.com; skalowalność; zarządzanie strategiczne; przemysł 4.0